2010
DOI: 10.1063/1.3467467
|View full text |Cite
|
Sign up to set email alerts
|

Co doping enhanced giant magnetocaloric effect in Mn1−xCoxAs films epitaxied on GaAs (001)

Abstract: A giant magnetocaloric effect was found in series of Mn1−xCoxAs films epitaxied on GaAs (001). The maximum magnetic entropy change caused by a magnetic field of 4 T is as large as 25 J/kg K around room temperature, which is about twice the value of pure MnAs film. The observed small thermal hysteresis is more suitable for practical application. Growing of layered Mn1−xCoxAs films with Co concentration changing gradually may draw layered active magnetic regenerator refrigerators closer to practical application.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…3,4 While the MCE is most frequently studied in bulk materials, there has been some effort recently to explore the MCE in nanoscale materials. [5][6][7][8][9][10][11][12] In Refs. 5 and 6 it was shown that finite size effects can detrimentally impact the magnetic entropy change in Gd/W multilayers.…”
mentioning
confidence: 99%
“…3,4 While the MCE is most frequently studied in bulk materials, there has been some effort recently to explore the MCE in nanoscale materials. [5][6][7][8][9][10][11][12] In Refs. 5 and 6 it was shown that finite size effects can detrimentally impact the magnetic entropy change in Gd/W multilayers.…”
mentioning
confidence: 99%
“…These values are higher than those of Codoped MnAs (25 J/kgK at 4 T), Fe-doped MnAs (42 J/kgK at 5 T) and comparable to that of Cu-doped MnAs (175 J/kgK at 5 T). [6][7][8][9] …”
Section: Resultsmentioning
confidence: 99%
“…4 On the other hand, a giant magnetic field-induced uniaxial strain of 0.7% in MnAs is also reported by Cherenko et al 5 Recently, the room temperature giant MCE was also obtained by substitution of Mn by Fe, Co, Cr, and Cu. [6][7][8][9] Cui et al reported that with increasing Si doping in MnAs 1Àx Si x , the thermal hysteresis is decreased to nearly zero (x > 0.06), and the maximum of the magnetic entropy change is maintained above 10 and 5 J/(kgK) at 5 T and 2 T, respectively. 10,11 In addition, they studied the effect of interstitial nitrogen on the phase transition and magnetocaloric behavior of MnAs 1Àx Si x N d (x ¼ 0.03, 0.06, and 0.09).…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, relatively smaller thermal/magnetic hysteresis than those possessing magnetostructural transition are generally revealed. In numerous materials presenting FOMT, Mn-based intermetallic compounds, such as MnFePAs(Si/Ge) [13,18], MnAs [20,21], Ni-Mn-based [9][10][11], and Mn(Co,Ni)Ge systems [12,14], have extensively been investigated owing to the low cost and higher magnetic moment of Mn atoms, sometimes even 4 µ B per Mn atom [18].…”
Section: Introductionmentioning
confidence: 99%